How Are n-3 LCPUFAs Antiarrhythmic? A Reassessment of n-3 LCPUFAs in Cardiac Disease - Andrew Ramadeen; Paul Dorian (Cardiology Research and Practice)
Long-chain n-3-polyunsaturated fatty acids (n-3 LCPUFAs), referring particularly to marine-derived eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been shown to be effective in treating arrhythmias in some clinical trials and animal studies. The mechanism for this effect of n-3 LCPUFAs is not well understood. Experimental studies and clinical trials published in the 1980s and 1990s suggested that n-3 LCPUFAs may be antiarrhythmic drugs, but more recent trials have not confirmed this. In this paper, we examine evidence for, and against, the direct antiarrhythmic action of n-3 LCPUFAs and suggest that antistructural remodeling effects of n-3 LCPUFAs may be more relevant in accounting for their clinical effects.